2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.486
|View full text |Cite
|
Sign up to set email alerts
|

Business Models of Developer Platforms in the Telecommunications Industry -- An Explorative Case Study Analysis

Abstract: Digital platforms are re-shaping organizations and markets. In particular, telecommunication companies are challenged to control digital platforms and to engage generative ecosystems. In order to provide a point of departure for future research, we conduct an explorative case study analysis to determine the state of the art of business models of telecommunication operators' developer platforms. The contribution of our study is three-fold, providing insights on business model design, platform control and compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Indeed, several researchers (e.g., Friedrich et al, 2015;Kuebel et al, 2014;Ovum, 2014) have shown that communications service providers are already committed and are taking steps towards digital transformation, but lack a clear path or guide. They all are taking divergent routes, in many cases changing course as they "try and learn" (Friedrich et al, 2015).…”
Section: A Digital Maturity Model For Telecommunications Service Provmentioning
confidence: 99%
“…Indeed, several researchers (e.g., Friedrich et al, 2015;Kuebel et al, 2014;Ovum, 2014) have shown that communications service providers are already committed and are taking steps towards digital transformation, but lack a clear path or guide. They all are taking divergent routes, in many cases changing course as they "try and learn" (Friedrich et al, 2015).…”
Section: A Digital Maturity Model For Telecommunications Service Provmentioning
confidence: 99%
“…Studies have shown that a decisive acceptance factor in the adaptation of smart home devices lies in the consumer's perception of security and control (Kuebel and Zarnekow, 2015). Trust is closely related to these constructs because it can help reduce uncertainty.…”
Section: Automated Purchasing Processesmentioning
confidence: 99%
“…A semistructured interview data-gathering approach is particularly relevant for innovations or experimental technologies in qualitative research [9], where interviewees are provided the freedom to elaborate on the interview guide. Seeking expert opinions for revealing consumer adoption insights is preferred in smart home research [1,9,60] as their adoption is still in the early stages. Moreover, experts are a rich information source since they manage marketing activities, including segmentation and targeting of potential consumers.…”
Section: Thematic Codingmentioning
confidence: 99%